2005
DOI: 10.1242/jcs.01599
|View full text |Cite
|
Sign up to set email alerts
|

Ciz1 promotes mammalian DNA replication

Abstract: Using a cell-free system that reconstitutes initiation of mammalian DNA replication, we identified a cyclin A-responsive protein, p21Cip1-interacting zinc finger protein 1 (Ciz1). In cell-free experiments, Ciz1 protein increases the number of nuclei that initiate DNA replication, and in intact cells GFP-tagged Ciz1 stimulates DNA synthesis, in both a wild-type and a p21Cip1 null background. Furthermore, mutation of a putative cyclin-dependent kinase phosphorylation site at threonines 191/2 alters Ciz1 activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
173
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 70 publications
(181 citation statements)
references
References 27 publications
7
173
1
Order By: Relevance
“…The exon 8–12 junction causes a frame-shift in the CIZ1 reading frame, leading to a premature translational stop codon in exon 13, despite the presence of downstream exons in CIZ1 -F mRNA (Figure 1(a)). CIZ1-F protein therefore lacks previously characterized functional domains, including the MH3-domain which anchors CIZ1 to the NM [8], and cyclin-binding motifs through which CIZ1 interacts with cyclin A, and which are essential for its DNA replication activity (Figure 1(b)) [6,7]. Other characterized sites of interaction with CDK2, p21 cip1 and YAP are also excluded [1517], while interaction with CDC6 [18], ERα [12], and dynein light chain [15] might be retained.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The exon 8–12 junction causes a frame-shift in the CIZ1 reading frame, leading to a premature translational stop codon in exon 13, despite the presence of downstream exons in CIZ1 -F mRNA (Figure 1(a)). CIZ1-F protein therefore lacks previously characterized functional domains, including the MH3-domain which anchors CIZ1 to the NM [8], and cyclin-binding motifs through which CIZ1 interacts with cyclin A, and which are essential for its DNA replication activity (Figure 1(b)) [6,7]. Other characterized sites of interaction with CDK2, p21 cip1 and YAP are also excluded [1517], while interaction with CDC6 [18], ERα [12], and dynein light chain [15] might be retained.…”
Section: Resultsmentioning
confidence: 99%
“…We and others have shown that CIZ1 is a NM protein, defined by its resistance to extraction of chromatin [3,8], which suggests that its function is connected to nuclear architecture, possibly contributing to the spatial regulation of nuclear processes [68,18,24]. Although the NM appears to be corrupted in certain types of cancer [25] previous work [26–28] and our own experiments indicate that MCF-7 cells retain a NM structure to some extent.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations